Osteoporosis: possible pathways involved and the role of natural phytoestrogens in bone metabolism - Zar, Chi Thent; Srijit Dass,; Pasuk Mahakkanukrauh,; Lanzotti, Virginia (Penerbit Universiti Kebangsaan Malaysia, 2019)
The incidence of post-menopausal osteoporosis is increasing globally. In post-menopausal osteoporosis, there is deficiency in oestrogen level resulting in bone loss and fractures. Bone formation is under the control of different hormones. In the present review, we highlight few pathways such as RANKL/RANK, apoptosis and Wnt/β-catenin signalling pathways and phytoestrogens involved in the bone metabolism. RANKL/RANK signalling is responsible for regulating the formation and activation of multinucleated osteoclasts from their precursors which is responsible for the survival of normal bone remodelling. Apoptosis regulates the development, growth and maintains the bone tissues. The Wnt pathway is an important pharmacological target for bone anabolic drugs and its future discovery. In today’s world, herbal remedies are used to treat post-menopausal osteoporosis as these products contain phytoestrogens. These phytoestrogens are oestrogen like compounds which influence bone metabolism. The phytoestrogens provide better therapeutic effect in reducing the RANKL, osteoclastogenesis, inflammatory markers, and increase the osteogenic markers in the bone cells or osteoblasts. We discuss the mechanism of action of few phytoestrogens such as genistein, daidzein and equol which are beneficial for improvement of the bone health. Daidzein enhances osteoblast growth via the upregulation of BMP expression in primary osteoblast cells and it is a potential antiosteoporotic agent. Genistein also possesses antioestrogenic property by virtue of its competitive binding to the same receptors as oestradiol. Equol regulates the bone loss via hemopoiesis and inflammatory cytokine production. Thus, phytoestrogens could be efficiently used as osteoprotective agents for the treatment of individuals with post-menopausal osteoporosis.